Identification of Fractional-Order Transfer Functions Using a Step Excitation - Jacyntho, Luiz Antonio; Teixeira, Marcelo Carvalho Minhoto [UNESP]; Assunção, Edvaldo [UNESP]; Cardim, Rodrigo [UNESP]; Galvão, Roberto Kawakami Harrop; Hadjiloucas, Sillas (Institute of Electrical and Electronics Engineers (IEEE), 2015)
This brief proposes a new method for the identification of fractional-order transfer functions based on the time response resulting from a single step excitation. The proposed method is applied to the identification of a 3-D RC network, which can be tailored in terms of topology and composition to emulate real-time systems governed by fractional-order dynamics. The results are in excellent agreement with the actual network response, yet the identification procedure only requires a small number of coefficients to be determined, demonstrating that the fractional-order modeling approach leads to very parsimonious model formulations.
Keywords: analog circuit simulation; Fractional order systems; RC circuits; system identification